model for computing date palm water requirements as affected by salinity - Sperling, Or; Or Shapira; Effi Tripler; Amnon Schwartz; Naftali Lazarovitch (Irrigation science, 2014)
Irrigation of crops in arid regions with marginal water is expanding. Due to economic and environmental issues arising from use of low-quality water, irrigation should follow the actual crop water demands. However, direct measurements of transpiration are scant, and indirect methods are commonly applied; e.g., the PenmanâMonteith (PM) equation that integrates physiological and meteorological parameters. In this study, the effects of environmental conditions on canopy resistance and water loss were experimentally characterized, and a model to calculate palm tree evapotranspiration ETcwas developed. A novel addition was to integrate water salinity into the model, thus accounting for irrigation water quality as an additional factor. Palm tree ETcwas affected by irrigation water salinity, and maximum values were reduced by 25Â % in plants irrigated with 4Â dSÂ mâ»Â¹and by 50Â % in the trees irrigated with 8Â dSÂ mâ»Â¹. Results relating the responses of stomata to the environment exhibited an exponential relation between increased light intensities and stomatal conductance, a surprising positive response of stomata to high vapor pressure deficits and a decrease in conductance as water salinity increased. These findings were integrated into a modified âJarvisâPMâ canopy conductance model using only meteorological and water quality inputs. The new approach produced weekly irrigation recommendations based on field water salinity (2.8Â dSÂ mâ»Â¹) and climatic forecasts that led to a 20Â % decrease in irrigation water use when compared with current irrigation recommendations.